[PP.24.02] MANAGEMENT OF ORAL ANTICOAGULANTS IN OUTPATIENTS WITH NONVALVULAR ATRIAL FIBRILLATION DAILY ATTENDED BY CARDIOLOGISTS. (September 2017) - Barrios, V.; Escobar, C.; Baron, G.; Doblas, Jj. Gomez; Parici, M.; Recalde, E.; Toril, J.; Chopo, Jm.; Rossi, P.; Monzerkhanji, M.
Abstract : Objective: To analyze the management of dabigatran and vitamin K antagonists in outpatients with nonvalvular atrial fibrillation in clinical practice in Spain. Design and method: This is an ongoing observational, prospective and multicenter study in which outpatients with nonvalvular atrial fibrillation daily attended by cardiologists in Spain that have started treatment with dabigatran or vitamin K antagonists in the last month are being included. All patients will be followed during 6 months. In this abstract, baseline data of the first 649 patients were presented. Results: Mean age of patients was 73.5 ± 9.5 years, and 56.4% of patients were men. Mean CHA2-DS2-VASc score was 3.6 ± 1.5 and mean HAS-BLED score 1.4 ± 1.1. Permanent atrial fibrillation was reported in 41.7% of patients, paroxysmal atrial fibrillation in 33.5% of patients and persistent atrial fibrillation in 24.8% of patients. With regard to treatment, 69.2% of patients were taking beta blockers, 22.6% amiodarone, 12.2% digoxin, 9.3% class IC antiarrhythmic drugs, 8.5% calcium channel blockers and 1.7% dronedarone. With regard to anticoagulant therapy, 505 patients were taking dabigatran (57.9% dabigatran 150 mg bid and 42.1% dabigatran 110 mg bid) and the remaining 144 patients vitamin K antagonists. The most important reason for choosing dabigatran 110 mg bid was advanced age (64.2%) followed by concern about bleeding risk (32.5%). Conclusions: Outpatients daily attended by cardiologists in Spain have a high risk of thromboembolic events, but a low/moderate risk of bleeding. The majority of patients are polymedicated. The main reason for prescribing dabigatran 110 mg bid was advanced age.